Penghasilan catan digital dalam pendidikan seni visual murid tingkatan empat / Azimah A. Samah - Azimah, A. Samah (2016)
Painting production requires consistency in cognitive and psychomotor skills. This is difficult to achieve if pupils have poor understanding in concepts and painting skills. Therefore, production of conventional painting should be given added value in a form of digital reproduction. The use of digital media can help to develop pupil’s visual imagery on four aspects of which are composition, color manipulation, interpretation and creativity. As such, a cognitive development theory-based study was carried out among pupils in order to explore the development of their visual imagery. Visual imagery ability is seen based on the production of digital painting and conventional painting. This study used a quantitative approach and was executed at two secondary schools in Kuala Langat and Sepang. A total of 53 pupils were involved in a quasi-experimental study in which 29 were among average achievers while 24 were low performers. All pupils were given treatment using digital equipment in producing painting. Each pupil was required to take a test on basic knowledge in computer, Adobe Photoshop application and fundamental visual arts. They also produced two digital paintings and two conventional paintings. Data from the tests and the paintings were analyzed using inferential statistical tests which were Manova independent sample test and Manova repeated measurement. In addition, data were also analyzed using correlation and multiple regression. Findings showed that knowledge in basic computer, knowledge in Adobe Photoshop application and visual arts fundamental were equal between the week and average groups . There was an increase in the development of pupils’ visual imagery in digital and conventional paintings on four aspects which are composition, color manipulation, interpretation and creativity. In addition, there was a significant relationship between achievement in digital painting and conventional painting. Pupils were able to construct a digital painting after treatment was given. It stimulated cognitive development that led to psychomotor movement. Changes were not only seen from the quality of the paintings but also the quality of cognitive change. Such intellectual development was a fusion of the mind, eyes and existing knowledge portrayed in the form of a painting. Nevertheless, the average achievers showed higher cognitive performance compared to the low achievers. This study aimed to assist teachers with appropriate strategies and medium in the teaching and learning of visual arts particularly in fine art. Pupils are able to maximize their cognitive development in producing painting based on their visual representation and visual imagery formation. Theoretically, this study is expected to further enhance the understanding of human cognitive systems and information processing that relate to visual imagery system.